2023
DOI: 10.3390/educsci13030303
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Software Design and Construction Teaching: A Systematic Literature Review

Abstract: Teaching in computing faces challenges in relation toconcerning technological changes and strategies to encourage student engagement with the teaching–learning process. In software engineering, specifically in the construction of the solution, these challenges are even greater due to technological changes and the evolution of applications. Based on this context, the objective of this work is to present the results of a systematic literature review on the knowledge areas that are central to the software constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The validation results were used to measure the performance of the two research models, and a comparison was carried out to find the model that had the best performance using accuracy confusion matrix analysis (Castro & Oliveira, 2023).…”
Section: Validation With Cross Validationmentioning
confidence: 99%
“…The validation results were used to measure the performance of the two research models, and a comparison was carried out to find the model that had the best performance using accuracy confusion matrix analysis (Castro & Oliveira, 2023).…”
Section: Validation With Cross Validationmentioning
confidence: 99%
“…The findings showed that co-teaching can contribute to spatial inclusion in mathematics education, implying that all students can be taught in the same class. (Gardesten, 2023).…”
Section: Co-teachingmentioning
confidence: 99%